Association of the oxidative balance score and chronic kidney disease: insights from the national health and nutrition examination survey 2009–2018 - Chen, Xinyun; Wu, Zheng; Hou, Xingyu; Yu, Wenhui; Gao, Chang; Gou, Shenju; Fu, Ping (Frontiers in Nutrition, 2024)
Oxidative stress plays a pivotal role in the pathogenesis of chronic kidney disease (CKD). The oxidative balance score (OBS) was devised to quantify the overall oxidative state, integrating pro-oxidant and antioxidant influences from both dietary intake and lifestyle practices. The aim of this study was to delve into the relationship between the OBS and CKD within the adult population of the United States. Methods: Utilizing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2009-2018, we derived the OBS from sixteen dietary and four lifestyle factors. We employed weighted multivariate regression to probe the link between OBS and CKD. Additionally, we undertook subgroup analyses and applied Restricted Cubic Spline Regression (RCS) for further data analyses. Results: This study encompassed 19,444 participants. Logistic regression analysis consistently demonstrated a protective effect of higher OBS on CKD. In Model 3, each unit increase in OBS was associated with a 2% reduction in the risk of CKD (95% CI: 0.97-0.99, p < 0.001) and a 4% reduction in the risk of reduced estimated glomerular filtration rate (eGFR) (95% CI: 0.95-0.98, p < 0.001). The highest OBS quintile (Q4) also showed significant reductions in the risk of CKD (OR: 0.66, 95% CI: 0.53-0.82, p < 0.001) and reduced eGFR (OR: 0.51, 95% CI: 0.37-0.69, p < 0.001) in Model 3. RCS analysis revealed a linear relationship between OBS and CKD. Subgroup analyses indicated significant associations between OBS and CKD in most subgroups, except for those without hypertension or with cardiovascular disease. Additionally, interaction analyses demonstrated that age, hypertension, and diabetes significantly modify the association between OBS and CKD risk. Conclusions: An elevated OBS, reflecting a predominance of antioxidants, correlates with a diminished CKD risk in the American adult demographic. These insights emphasize the potential influence of oxidative equilibrium on the development of CKD.